2008
DOI: 10.1007/s00417-008-0980-7
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of vitreous surgery

Abstract: Vitreous surgery has various physiological and clinical consequences, both beneficial and harmful. Vitrectomy reduces the risk of retinal neovascularization, while increasing the risk of iris neovascularization, reduces macular edema and stimulates cataract formation. These clinical consequences may be understood with the help of classical laws of physics and physiology. The laws of Fick, Stokes-Einstein and Hagen-Poiseuille state that molecular transport by diffusion or convection is inversely related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
202
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(209 citation statements)
references
References 137 publications
(206 reference statements)
0
202
2
5
Order By: Relevance
“…The gel state of the vitreous body assures that the movement of molecules within it occurs only by diffusion [34,35]. Measurements made with oxygen microelectrodes or nuclear magnetic resonance spectroscopy showed that oxygen diffuses into the vitreous from the retinal vessels [19,36].…”
Section: The Mechanisms That Maintain the Low-oxygen Environment Aroumentioning
confidence: 99%
“…The gel state of the vitreous body assures that the movement of molecules within it occurs only by diffusion [34,35]. Measurements made with oxygen microelectrodes or nuclear magnetic resonance spectroscopy showed that oxygen diffuses into the vitreous from the retinal vessels [19,36].…”
Section: The Mechanisms That Maintain the Low-oxygen Environment Aroumentioning
confidence: 99%
“…Stimulating factors might be the surgically induced PVD, peeling of epiretinal membranes, gas tamponade, and increased oxygenation following vitrectomy. 8 The additional ILM peeling in the here reported case might have enhanced the stimulation, resulting in an almost complete phagocytosis of drusen. Remarkably, postoperative new drusen formation spared the central area where compact drusen material had been present preoperatively.…”
Section: Case Reportmentioning
confidence: 68%
“…There is, however, evidence of a more intricate and purposeful composition [10] with important physiological implications on the micro-milieu of the retina including the upkeep of salt and nutrient gradients, physical support and more [35,36]. An ideal vitreous substitute would replicate these influences on the neuroretina and surrounding tissues as well as provide a tamponading effect after vitrectomy [10].…”
Section: Our Previous Results and Our Hypothesismentioning
confidence: 99%